2021
DOI: 10.1371/journal.ppat.1009116
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide fitness analysis of group B Streptococcus in human amniotic fluid reveals a transcription factor that controls multiple virulence traits

Abstract: Streptococcus agalactiae (group B Streptococcus; GBS) remains a dominant cause of serious neonatal infections. One aspect of GBS that renders it particularly virulent during the perinatal period is its ability to invade the chorioamniotic membranes and persist in amniotic fluid, which is nutritionally deplete and rich in fetal immunologic factors such as antimicrobial peptides. We used next-generation sequencing of transposon-genome junctions (Tn-seq) to identify five GBS genes that promote survival in the pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 139 publications
(207 reference statements)
0
15
0
Order By: Relevance
“…MrvR; deletion of mrvR reduced GBS survival in amniotic fluid and impaired biofilm formation. Pregnant mice vaginally-infected by MrvRnull GBS exhibited normal vaginal persistence and consistent ascending infection, but these mice did not experience PTB (Dammann et al, 2021), suggesting that MrvR may mainly promote bacterial survival in vivo.…”
Section: Gbs Trafficking Into the Amniotic Cavitymentioning
confidence: 98%
“…MrvR; deletion of mrvR reduced GBS survival in amniotic fluid and impaired biofilm formation. Pregnant mice vaginally-infected by MrvRnull GBS exhibited normal vaginal persistence and consistent ascending infection, but these mice did not experience PTB (Dammann et al, 2021), suggesting that MrvR may mainly promote bacterial survival in vivo.…”
Section: Gbs Trafficking Into the Amniotic Cavitymentioning
confidence: 98%
“…Native CRISPR-Cas systems can be predicted from the sequenced genome or proteome using computer software ( Couvin et al, 2018 ; Chai et al, 2019 ), aiding in CRISPRi/a tool selection for novel strains. Alternatively, the native system can be engineered to create a CRISPRi/a tool via genetic manipulation, such as the deletion of the native cas2/3 or cas3 gene responsible for cleavage in Type I-F systems ( Zheng et al, 2019 ; Qin et al, 2021 ; Xu et al, 2021 ) or mutating the native cas9 sequence for Type II systems ( Shields et al, 2020 ; Dammann et al, 2021 ). Anti-CRISPR proteins, which inhibit CRISPR systems through a variety of mechanisms ( Pawluk et al, 2018 ), may require deletion or disruption before a heterologous CRISPRi/a tool can be expressed ( Xu et al, 2021 ).…”
Section: Requirements and Challenges To Establish Crispri/a In Non-mo...mentioning
confidence: 99%
“…A previous study identified the nucleotide excision repair gene uvrA as the genetic determinant of desiccation tolerance of the Streptococcus pneumoniae by Tn-seq ( 18 ). Moreover, five novel Streptococcus agalactiae genes that promote survival in the presence of human amniotic fluid were identified by Tn-seq ( 19 ).…”
Section: Introductionmentioning
confidence: 99%